Effects of moderate variations in macronutrient composition on weight loss and reduction in cardiovascular disease risk in obese, insulin-resistant adults - McLaughlin, Tracey; Carter, Susan; Lamendola, Cindy; Abbasi, Fahim; Yee, Gail; Schaaf, Patricia; Basina, Marina; Reaven, Gerald (The American journal of clinical nutrition, 2006)
BACKGROUND: Obese, insulin-resistant persons are at risk of cardiovascular disease. How best to achieve both weight loss and clinical benefit in these persons is controversial, and recent reports questioned the superiority of low-fat diets. OBJECTIVE: We aimed to ascertain the effects of moderate variations in the carbohydrate and fat content of calorie-restricted diets on weight loss and cardiovascular disease risk in obese, insulin-resistant persons. DESIGN: Fifty-seven randomly assigned, insulin-resistant, obese persons completed a 16-wk calorie-restricted diet with 15% of energy as protein and either 60% and 25% or 40% and 45% of energy as carbohydrate and fat, respectively. Baseline and postweight-loss insulin resistance; daylong glucose, insulin, and triacylglycerol concentrations; fasting lipid and lipoprotein concentrations; and markers of endothelial function were quantified. RESULTS: Weight loss with 60% or 40% of energy as carbohydrate (5.7 ± 0.7 or 6.9 ± 0.7 kg, respectively) did not differ significantly, and improvement in insulin sensitivity correlated with the amount of weight lost (r = 0.50, P < 0.001). Subjects following the diet with 40% of energy as carbohydrate had greater reductions in daylong insulin and triacylglycerol (P < 0.05) and fasting triacylglycerol (0.53 mmol/L; P = 0.04) concentrations, greater increases in HDL-cholesterol concentrations (0.12 mmol/L; P < 0.01) and LDL particle size (1.82 s; P < 0.05), and a greater decrease in plasma E-selectin (5.6 ng/L; P = 0.02) than did subjects following the diet with 60% of energy as carbohydrate. CONCLUSIONS: In obese, insulin-resistant persons, a calorie-restricted diet, moderately lower in carbohydrate and higher in unsaturated fat, is as efficacious as the traditional low-fat diet in producing weight loss and may be more beneficial in reducing markers for cardiovascular disease risk.